Controls on the geotechnical properties of plastic-bonded pavement blocks produced by artisanal means in Bamenda, Cameroon - Bertrand Tatoh Aziwo; Moses Kuma Mbuh; Irene Bongsiysi Bame; Paul Venyite; Moyouwou Amadou Njoya; Fidelis Toke Ntam; M.V. Nsongka; Ndigui Billong (Engineering Science and Technology, an International Journal)
Recycling plastic wastes as binder in pavement blocks can be adopted as a means of managing municipal plastic wastes in Cameroon. The variability in the geotechnical properties of plastic-bonded pavement blocks in the literature suggest a wide interplay of controlling factors that need to be clarified. This study evaluates the controls on the geotechnical properties of pavement blocks produced by artisanal means, using various aggregate (washed weathered granite sand- WS, 0/5 basalt quarry sand-QS & 5/15 basalt gravel -G) and aggregate combinations (50WS50QS, 50WS50G, 50QS50G, 70WS20QS10G) with varying low- and high-density polyethylene (L/HDPE) and polyethylene terephthalate (PET) plastic waste content. Geotechnical tests were carried out on aggregates and samples of various formulations. An average compressive strength of 32.97 MPa, water absorption of 2.27 % and an abrasion index of 0.07 was obtained at 27.5 % PET for 50WS50QS, which meets the recommended requirements of pavement blocks for pedestrian and light vehicular traffic according to ASTM C-902-22, NF EN 1338:2004 and SNI 03-0691-1996 standards. From the results, the geotechnical properties are influenced by nature and size of aggregate, type and amount of plastic-binder and production method. Finding the optimal plastic-binder content for a given aggregate and plastic type is key in achieving optimal geotechnical properties. The results can serve as a guide for the production of quality plastic-bonded pavement blocks especially in nations where a bulk of their construction materials are produced by artisanal means.